Peran Public Relations dalam Pelayanan Publik di Badan Kepegawaian Negara (BKN) Pusat - Indah Permata Aryani; Wiratri Anindhita; Dini Safitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Every government institution must maintain a harmonious relationship with the community. As the front guard in establishing relationships between an organization and its public, public relations has a very important role in providing quality and satisfying public services for the community. The State Civil Service Agency as an institution that has responsibility for the management of the State Civil Apparatus makes public service one of the priorities that has targets that must be effective and efficient so that it must be taken seriously. This study aims to find out what roles are played by Public relations in carrying out public services at the National Civil Service Agency. This study used data collection methods through interviews and the selection of research informants through purposive sampling, which were in accordance with the selected criteria and were indeed relevant to the research problem, namely Youth Public relations Officers (Sub-coordinators). The results of this study indicate that the role of public relations in public services at the State Personnel Agency plays an important role in maintaining the positive image of the State Personnel Agency by publicizing all activities carried out by the State Personnel Agency, providing information, inviting scheduled hearings if problems occur and requires solutions by discussing directly, as well as ensuring that the public services of the State Civil Service Agency meet the required standards and can be used as evaluation material for improvement and enhancement of public services in the State Personnel Agency.